2013
DOI: 10.1002/biot.201300227
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous biphasic cancer cell migration assay enables robust, high‐throughput screening of anti‐cancer compounds

Abstract: Migration of tumor cells is a fundamental event implicated in metastatic progression of cancer. Therapeutic compounds with the ability to inhibit the motility of cancer cells are critical for preventing cancer metastasis. Achieving this goal requires new technologies that enable high-throughput drug screening against migration of cancer cells and expedite drug discovery. We report an easy-to-implement, robotically operated, cell migration microtechnology with the capability of simultaneous screening of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Therefore, ATPS is solely used as a patterning medium to generate spheroids. Micropatterning with ATPS has additionally facilitated the generation of cancer cell niches for migration studies …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ATPS is solely used as a patterning medium to generate spheroids. Micropatterning with ATPS has additionally facilitated the generation of cancer cell niches for migration studies …”
Section: Resultsmentioning
confidence: 99%
“…Drop diameter data from experiments at air volumes of 0.3–1.5 μl follow a linear trend, indicating that data are normally distributed. (30, 31) Different slopes of the lines indicate differences between standard deviations of data from these air volumes. (32) We confirmed that data obtained for drop diameter by varying each of the three parameters within the pre-defined range of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After 12 hours of incubation, the ATPS was replaced with growth medium only (control) or medium containing a test compound. The area of the cell-excluded gap within well plates averaged to 3.33 ± 0.09 mm 2 27. …”
Section: Methodsmentioning
confidence: 99%
“…We have previously evaluated this robotic technology for high throughput compound screening against cell migration and shown that it consistently returns a Z ′ factor of greater than 0.7, demonstrating its quality and robust performance. 27 Using this migration technology, our screening identified several natural compounds that effectively blocked motility of cells. Subsequent molecular analysis showed that phytochemicals interfered with dysregulated kinase signaling and scavenged excessive intracellular free radicals in TNBC cells.…”
Section: Introductionmentioning
confidence: 99%